2005
DOI: 10.1021/jf040295q
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Composition of Grape Seed Oils Extracted by Supercritical Carbon Dioxide and Petroleum Ether:  Varietal Effects

Abstract: Grape seed has a well-known potential for production of oil as a byproduct of winemaking and is currently produced as a specialty oil byproduct of wine manufacture. Seed oils from eight varieties of grapes crushed for wine production in British Columbia were extracted by supercritical carbon dioxide (SCE) and petroleum ether (PE). Oil yields by SCE ranged from 5.85 +/- 0.33 to 13.6 +/- 0.46% (w/w), whereas PE yields ranged from 6.64 +/- 0.16 to 11.17 +/- 0.05% (+/- is standard deviation). The oils contained al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
138
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(182 citation statements)
references
References 10 publications
(16 reference statements)
30
138
1
4
Order By: Relevance
“…They reported that the oil content of seeds obtained from different grape cultivars ranged from 9.90 to 20.00%. Similarly, Beveridge et al (2005) using two extraction methods found that grape seed oil yields ranged from 5.85 to 13.6% and 6.64 to 11.17% with supercritical carbon dioxide and petroleum ether extractions, respectively. On the other hand, the oil contents of pomace varied from 5.47 to 8.66%.…”
Section: Oil Contentmentioning
confidence: 96%
“…They reported that the oil content of seeds obtained from different grape cultivars ranged from 9.90 to 20.00%. Similarly, Beveridge et al (2005) using two extraction methods found that grape seed oil yields ranged from 5.85 to 13.6% and 6.64 to 11.17% with supercritical carbon dioxide and petroleum ether extractions, respectively. On the other hand, the oil contents of pomace varied from 5.47 to 8.66%.…”
Section: Oil Contentmentioning
confidence: 96%
“…Linoleic acid (omega-6) is one of two essential fatty acids which can not be synthesized in the body and it is the precursor of a family of other fatty acids such as arachidonic acid and gamma-linolenic acid 16,17) . Beveridge et al,used two extraction methods; found that GSO is ranged from 5.85 to 13.6% and 6.64 to 11.17% with supercritical CO 2 and petroleum ether extraction respectively 18) . Grape seed and pomace oils had nearly similar FA profile with higher linoleic acid and very low linolenic acid content that make the oil more resistant to autoxidation.…”
mentioning
confidence: 99%
“…A hydro separation method (G:V = 1:3) was conducted in order to separate tomato seeds from the rest of the waste material, where G -tomato solid waste (skin and seed), V -distillated water. Through the hydro separation process it was established that seeds constitute 37,9 % (wt) of the waste material [5]. After the hydro separation procedure, obtained seeds were submitted to ambient temperature drying process in absence of sunlight.…”
Section: Methodsmentioning
confidence: 99%